Trouble in Anatolia - Nick R Anthonisen (Canadian Respiratory Journal, 2004)
In this issue of the Canadian Respiratory Journal, Gulmez et al (pages 287-290) review the presentation, management and outcome of malignant mesothelioma in central Anatolia, Turkey. There is nothing particularly new about the disease here; it presents with chest pain, dyspnea and pleural effusion, is diagnosed by biopsy and has a miserable outcome whatever is done for it, just like malignant mesothelioma in Canada. Mesothelioma in Anatolia is unusual in that it is very common, with an approximately equal sex distribution, and frequently occurs in relatively young people. The reasons for this are not a mystery. Anatolia is a volcanic area; there is a lot of asbestos on or near the surface, and it is widely used as construction material, in painting, and as insulation (pages 287-290)! Asbestos related disease is due to environmental, not occupational exposure, and exposure is more intense and occurs at an earlier age than in Canada. Not only that, but some areas of Anatolia are rich in erionite, and people build homes in and on erionite-bearing rocks. Erionite is apparently something like asbestos but worse in terms of carcinogenicity (1), perhaps because its crystals have large surface areas, and areas with erionite have an even higher incidence of mesothelioma.